2015
DOI: 10.1007/s00520-015-2984-2
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss with mindful eating in African American women following treatment for breast cancer: a longitudinal study

Abstract: Purpose Women with higher body mass index (BMI) following breast cancer (BC) treatment are at higher risk of BC recurrence and death than women of normal weight. African American (AA) BC patients have the highest risk of BC recurrence and gain more weight after diagnosis than their white counterparts. The purpose of this study was to evaluate the association between a mindful eating intervention and weight loss in AA women following chemotherapy for BC. Methods A single-group 24-week longitudinal pilot study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 29 publications
1
65
0
2
Order By: Relevance
“…Studies that used a combination of informal and formal meditation practice showed higher effects ( n = 6; Hedge's g = .55; CI 95% [.32, .77], p < .00001) than formal meditation practice alone ( n = 4; Hedge's g = .46; 95% CI [.10, .83], p < .05). The effects of informal mindfulness exercises alone on weight loss were not significant ( n = 6; p = .17). Effects of MBIs on weight loss were maintained at follow‐up ( n = 6; Hedge's g = .58; 95% CI [.12, 1.03], p < .05).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Studies that used a combination of informal and formal meditation practice showed higher effects ( n = 6; Hedge's g = .55; CI 95% [.32, .77], p < .00001) than formal meditation practice alone ( n = 4; Hedge's g = .46; 95% CI [.10, .83], p < .05). The effects of informal mindfulness exercises alone on weight loss were not significant ( n = 6; p = .17). Effects of MBIs on weight loss were maintained at follow‐up ( n = 6; Hedge's g = .58; 95% CI [.12, 1.03], p < .05).…”
Section: Resultsmentioning
confidence: 88%
“…46; 95% CI [.10, .83], p < .05). The effects of informal mindfulness exercises (53,63,73,(77)(78)(79)(80) alone on weight loss were not significant (n = 6; p = .17). Effects of MBIs on weight loss were maintained at follow-up (n = 6; Hedge's g = .58; 95% CI [.12, 1.03], p < .05).…”
Section: Weight Lossmentioning
confidence: 95%
See 1 more Smart Citation
“…Being overweight is a complex factor with variable effect on the risk of breast cancer, depending on the age of subjects (Protani et al, 2010, Munsell et al, 2014Chung et al, 2016). For post-menopausal women obesity is a risk factor, whereas for younger women this factor is virtually insignificant (Dieli-Conwright et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For post-menopausal women obesity is a risk factor, whereas for younger women this factor is virtually insignificant (Dieli-Conwright et al, 2016). Chung et al, (2016) emphasises that overweight women above the age of 60 have a higher risk of the cancer risk. Our results are very alarming.…”
Section: Discussionmentioning
confidence: 99%